Living with the world heritage. An ethnographic study of the ancient city of Nessebar, Bulgaria - Luleva, Ana (Institute of Ethnography, SASA, Belgrade, 2018)
Since the mid-1950s the Ancient city of Nessebar has had the status of national cultural heritage; in 1983 it was inscribed in the World heritage list of UNESCO. The article makes an attempt to study the regimes of using of and living in the city - world cultural heritage in two different political and economic contexts. The pressure of the tourism industry on the value, which was visible even in the years of the late state socialism, became irresistible after 1989 in the context of the liberalised market economy, the interests of the private investors and the accepted as part of the "normal" market order corrupt practices of the institutions that are responsible for the safeguarding and management of the cultural heritage. The ethnographic study argues that intertwined in a Gordian knot around the central question for the residents of the ancient city of Nessebar, viz. the occupation of the city, which has been declared a world heritage site, are issues like trust and distrust in the institutions, the experience of abiding by formal and informal rules for operation with private property, the notions of social justice, local identity, the use of the cultural heritage as symbolic capital by different social actors and its transformation into economic one, with the conflicting interconnection between tourist industry and cultural heritage.